First count the cost: Privatizing urban waste management services in Sub- Saharan Africa. - Osei-Kojo, A. (My University, 2016)
While privatisation has benefits, it must be approached with caution. Using qualitative methods, this article presents scenarios for consideration in privatising urban waste management in sub-Saharan Africa. This study employed purposive sampling in organising relevant literature and also used secondary data from journal articles, government reports and documents for analyses. Results indicate that privatisation of urban waste management services should consider the following: the possibility of a market failure; corruption in the private sector, poor service delivery; and prevalence of inefficiency. This study has implications for city managers and planners in deciding whether or not to privatise urban waste management services in sub-Saharan Africa.